The role of an elastic interphase in suppressing gas evolution and promoting uniform electroplating in sodium metal anodes - Gong, C; Pu, SD; Zhang, S; Yuan, Y; Ning, Z; Yang, S; Gao, X; Chau, C; Li, Z; Liu, J; Pi, L; Liu, B; et al. (Royal Society of Chemistry, 2023)
Ether solvent based electrolytes exhibit excellent performance with sodium battery anodes, outperforming the carbonate electrolytes that are routinely used with the analogous lithium-ion battery. Uncovering the mechanisms that facilitate this high performance for ether electrolytes, and conversely diagnosing the causes of the poor cycling with carbonate electrolytes, is crucial for informing the design of optimized electrolytes that promote fully reversible sodium cycling. An important contributor to the performance difference has been suggested to be the enhanced elasticity of the ether-derived solid–electrolyte interphase (SEI) layer, however experimental demonstration of exactly how this translates to improving the microscopic dynamics of a cycled anode remain less explored. Here, we reveal how this more elastic SEI prevents gas evolution at the interface of the metal anode by employing operando electrochemical transmission electron microscopy (TEM) to image the cycled electrode–electrolyte interface in real time. The high spatial resolution of TEM imaging reveals the rapid formation of gas bubbles at the interface during sodium electrostripping in carbonate electrolyte, a phenomenon not observed for the higher performance ether electrolyte, which impedes complete Na stripping and causes the SEI to delaminate from the electrode. This non-conformal and inflexible SEI must thus continuously reform, leading to increased Na loss to SEI formation, as supported by mass spectrometry measurements. The more elastic ether interphase is better able to maintain conformality with the electrode, preventing gas formation and facilitating flat electroplating. Our work shows why an elastic and flexible interphase is important for achieving high performance sodium anodes.